The Influence of Price, Service Quality and Trust on Repurchase Decisions with Consumer Satisfaction as an Intervening Variable in Bandrek Sergei MSMEs - Aflah, Nadhrah Al; Nuri Aslami; Budi Dharma (Dinasti Publisher, 2024)
The business world has become increasingly competitive lately. Business people must optimize their organizational performance to compete in the global market amidst an increasingly tight competitive environment. MSMEs or micro, small and medium enterprises are very important for economic growth and development in both industrial and developing countries, such as Indonesia. MSMEs have a function in Indonesia apart from contributing to economic growth and development. UMKM Banderk Sergai is a product business in the form of packaged instant bandrek herbal drinks that has been running since 2013. This UMKM has consumers who make repeat purchases from various cities starting from Aceh, Tebing Tinggi, Sei Rampah, Perbaungan, Lubuk Pakam, Tanjung Morawa, Medan, Deli Tua, and Binjai and there are still fluctuations in Banderk Sergai MSMEs as seen through income from 2018-2022. This research uses quantitative methods using a sample of 102 consumers at Bandrek Sergei MSMEs. The results of this finding are that repurchase decisions are strongly influenced by price and service quality, but not by trust. Then, although service quality has a big impact on customer happiness, price and trust have little effect on it. Repurchase decisions are also significantly influenced by customer satisfaction. Finally, although service quality and trust do not have a significant effect on consumer satisfaction through repeat purchase decisions, price has a significant positive effect on satisfaction. So the suggestion from this research is that Bandreak Sergai MSMEs should further improve service and trust to consumers regarding the products offered so that they continue to increase sales and consumers from Bandrek Sergai MSMEs continue to make repeat purchases in the long term.